Reviewing the role of families in student career planning - Hariko, Rezki; Anggriana, Tyas Martika (Konselor, 2019)
Mistakes in choosing a career and work are very common phenomena occurring in individuals today. This is generally an estuary from not implementing a good career plan, starting from an early age to the process of education in college. Career plan needs to be done early by each individual so that they have the ability to understand information about themselves, information about career goals and realistic reasoning in understanding their own information and career goals. This research is a library research, by searching, reading, studying, and analyzing the content of books and supported by various literature related to them. Based on the research concluded that parents are one of the external factors that carry a large role in providing social support for the development of individual career plan. In particular, parents play a role in providing social support in the form of emotional, appraisal, informational and instrumental support.